(untitled) (Latakia University (formerly Tishreen)Journal for Research and Scientific Studies - Economic and Legal Sciences Series, 2026)
This study examines the role of strategic planning in enhancing the geopolitical power of emerging states, using India as an empirical case study. The research is based on the central hypothesis that long-term strategic planning constitutes a critical mechanism for transforming economic capabilities into effective geopolitical power within the international system. The study employs an integrated analytical approach combining theoretical analysis from the perspectives of geopolitics and international political economy with quantitative economic analysis of key indicators such as GDP growth, investment flows, and international trade performance in India over recent decades. The findings indicate that institutional transformation in India’s planning system—particularly after the establishment of NITI Aayog—has significantly improved the effectiveness of development policies and strengthened the linkage between economic growth and geopolitical positioning. The results also reveal a positive relationship between economic performance indicators and the expansion of India’s geopolitical influence, particularly within the Indo-Pacific region. The study concludes that strategic planning plays a decisive role in converting economic potential into geopolitical power, and that the Indian experience represents an important model for emerging powers seeking to enhance their position in the contemporary international system.